Binding Mechanisms in Visual Perception and Their Link With Neural Oscillations: A Review of Evidence From tACS - Ghiani, Andrea; Maniglia, Marcello; Battaglini, Luca; Melcher, David; Ronconi, Luca (Frontiers in Psychology, 2021)
Neurophysiological studies in humans employing magneto- (MEG) and electro- (EEG) encephalography increasingly suggest that oscillatory rhythmic activity of the brain may be a core mechanism for binding sensory information across space, time and object features to generate a unified perceptual representation. To distinguish whether oscillatory activity is causally related to binding processes or is on the contrary a mere epiphenomenon, one possibility is to employ neuromodulatory techniques such as transcranial alternating current stimulation (tACS). tACS has seen a rising interest because of its potential for modulating brain oscillations in a frequency-dependent manner. In the present review, we critically summarize current tACS evidence for a causal role of oscillatory activity in spatial, temporal and feature binding relevant for visual perception. For temporal binding, the emerging picture supports a causal link with the power and frequency of occipital alpha rhythms (8-12 Hz), while at present there is no consistent evidence that the phase of occipital tACS can modulate temporal binding processes. Feature binding was found to be influenced by occipital alpha tACS in the only study available. When considering spatial binding, parietal areas seem to be the main target for studies that successfully modulated oscillatory activity and behavioral performance, with the main rhythms causally linked to spatial binding identified in the theta (~7 Hz) and beta (~18 Hz) frequency bands. Finally, spatio-temporal binding has been directly modulated by parieto-occipital gamma tACS (~40-60 Hz). Nonetheless, negative or partial results have also been observed, suggesting methodological limitations that should be addressed in future research. Overall, the emerging picture seems to support a causal role of brain oscillations in binding processes and, consequently, a certain degree of plasticity for shaping binding mechanisms in visual perception, which if proved to have long lasting effects can find applications in different clinical populations.